EVALUATION OF THE ANALGESIC AND FUNCTIONAL IMPROVEMENT EFFICACY OF ELECTROACUPUNCTURE, ACUPRESSURE MASSAGE COMBINED WITH SHOCKWAVE THERAPY IN PATIENTS WITH DEGENERATIVE SCIATICA (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the treatment outcomes of electroacupuncture, acupressure massage combined with shockwave therapy for sciatica due to lumbar spinal degeneration. To monitor for adverse effects of the method.Subject and methods: A clinical trial was conducted on 60 patients definitively diagnosed with sciatica due to lumbar spinal degeneration according to modern medicine, and classified as Yao Jue Tong (lumbar and leg pain) due to cold-dampness combined with deficiency of Liver and Kidney according to traditional medicine. The patients were divided purposively into two groups. Control group (n = 30): treated with electroacupuncture and acupressure massage. Study group (n = 30): treated with electroacupuncture, acupressure massage combined with shockwave therapy. The treatment course lasted 20 days. The results were compared between pre-treatment and post-treatment, and compared with the control group.Results: The mean age of the patients was 60,33 ± 10,66 years, with a higher proportion of females than males (34/60 versus 26/60). The treatment results showed that after 20 days of treatment, the combination of electroacupuncture, acupressure massage, and shockwave therapy improved the VAS score from 5,33 ± 0,6 to 1,03 ± 0,56 points. The method effectively improved the range of motion (ROM) of the lumbar spine, achieving a good treatment efficacy rate for: flexion 26.7%, extension 40%, lateral bending 30%, rotation 40%. Furthermore, it improved the Schober index from 11,13 ± 0,7 cm to 13,73 ± 0,58 cm, and improved the Lasègue from 50,30 ± 5,13 degree lên 72,20 ± 5,42 degree. No patient recorded a poor treatment efficacy. The difference between pre- and post-treatment, and the comparison with the control group, was statistically significant (p < 0.05). No adverse effects of the method were recorded during the entire treatment course.Conclusion: The combination of electroacupuncture, acupressure massage, and shockwave therapy demonstrated significantly better analgesic and functional improvement effects compared to the control group, with p < 0.05. Adverse effect monitoring: the method is safe, and no adverse effects were recorded throughout the study.
Keywords: Sciatica, shockwave therapy, pain relief, degenerative spine.